Certain Subclass of Analytic and Multivalent Functions Defined by Using a Certain Fractional Derivative Operator - Aouf, M. K.; Frasin, B. A. (Sarajevo Journal of Mathematics, 2024)
Making use of a certain operator of fractional derivative, a new subclass F_λ (n,p,α ,μ ) of analytic and p-valent functions with negative coefficients is introduced and studied here rather systematically. Coefficient estimates, a distortion theorem and radii of p-valently close-to-convexity, starlikeness and convexity are given. Finally several applications involving an integral operator and a certain fractional calculus operator are also considered. 2010 Mathematics Subject Classification. 30C4